Sample taking problems in measuring actual histamine levels of human gastroduodenal mucosa: specific and general relevance in clinical trials on peptic ulcer pathogenesis and selective proximal vagotomy. Issue 11 (November 1985) - Thon, K P; Lorenz, W; Ohmann, C; Weber, D; Rohde, H; Röher, H D
Abstract : Changes in histamine storage in the oxyntic mucosa of duodenal ulcer patients and their reversal by vagotomy and the histamine H2-antagonist cimetidine supported the hypothesis that histamine could be a causal factor in peptic ulcer pathogenesis. The specificity of these findings was impaired by problems in biopsy taking, however, and in the preparative steps before measuring the actual histamine contents in all parts of the gastric mucosa and in the duodenum. A prospective trial was carried out in 190 patients to identify these sources of bias and to overcome them by appropriate study designs. Usually a direct correlation was found between weight of biopsy and mucosal histamine content. This problem was solved by selecting a biopsy forceps producing smaller variations in sample size, by limiting the time of cold ischaemia to four to five minutes only and by taking three biopsy specimens for each single histamine value. The actual histamine content of mucosal biopsies remained constant for about four to five minutes only. The 'disappearance' rate was faster in control subjects than in duodenal ulcer patients. Hence by variation of the cold ischaemia time any artefacts of differences between mucosal histamine levels in controls and duodenal ulcer patients could be produced. Using the optimised sample taking procedure mucosal histamine contents of several gastric regions and the duodenal bulb were measured in 24 patients with duodenal ulcer, after selective proximal vagotomy without drainage and in control subjects without any stomach disease (randomised controlled trial). The histamine content was lower in all parts of the upper gastrointestinal tract in duodenal ulcer patients than in controls and was raised again in all regions after selective proximal vagotomy. As the most likely hypothesis it is suggested that vagal reflexes with afferent fibres coming from the oxyntic mucosa stimulate histamine release in duodenal ulcer patients by efferent peptidergic neurones to all parts of the stomach and the duodenum where the ulcer lesion is situated.